(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The article examines the transformations and declinations of informed consent in the context of the Covid-19 pandemic, analyzing the bioethical discussion and in particular international and national documents with bioethical and biolegal relevance, both of institutional bodies and bioethics committees. In particular, informed consent is analyzed in the context of experimentation with treatments and vaccines, the use of biological samples and the processing of personal data.